Interaction Between the Principles of Expediency and Thoroughness as well as Safeguarding of Human Rights in the Procedure for Issuing a Court Penal Order - Skripkutė, Greta (Teisė, 2026)
This article examines the relationship between the principles of expediency and thoroughness in the procedure for issuing a court penal order, as well as the safeguarding of the rights of the suspect (accused) when especially applying the principle of thoroughness. The analysis demonstrates that, up to the point at which the prosecutor submits the statement to the court, the principles of expediency and thoroughness interact in a manner analogous to that in ordinary criminal proceedings, namely that evidence is collected comprehensively while avoiding undue delay in the criminal process. However, once the court receives the statement of the prosecutor – and particularly when it decides to issue a court penal order – the principle of expediency assumes exceptional significance. At the same time, the principle of thoroughness is not negated, given its intrinsic link to establishing material truth; rather, it is more prominently manifested prior to the submission of the prosecutor’s statement to the court and during proceedings conducted under the ordinary, rather than simplified, procedural framework. The article also assesses the safeguarding of the rights of the suspect (accused) through the benefits granted to the suspect, as revealed through the application of the principle of thoroughness. Research shows that even benefits (a lenient sentence) can cause damage, which is why the suspect (accused) needs safeguards.
Keywords: principle of expediency; principle of thoroughness; procedure for issuing a court penal order; safeguarding of the rights of the suspect (accused)